Patients with endometrial cancer continue to lack understanding of their risks for cancer - Subhjit Sekhon; L. Stewart Massad; Andrea R. Hagemann; Rebecca Dick; Andrea Leon; Abigail S. Zamorano; Premal H. Thaker; Carolyn K. McCourt; David G. Mutch; Matthew A. Powell; Lindsay M. Kuroki (Elsevier, 2019)
It is unclear if endometrial cancer (EC) patients are aware of their modifiable risk factors. We administered a 33-item questionnaire to EC patients at a university-based cancer center to assess their understanding of how comorbidities and lifestyle/sexual behaviors impact their cancer risk. We also inquired about their access to a primary care physician (PCP). Pearson's χ2 test or Fisher's exact test were used to assess differences in understanding based on a dichotomized Charlson comorbidity score, <7 vs ≥7. Of the 50 surveyed women (81% response rate), 39 reported hypertension (80%) and 36 (72%) diabetes. All had a PCP. Most were aware that obesity contributes to diabetes (43/48, 90%), hypertension (42/48, 88%), and heart attack (42, 88%), but only 19/49 (39%) knew that EC is more common in overweight/obese women. More than half lacked understanding of the following risks including modifiable risk factors-unhealthy diet (31, 62%), hormone replacement therapy (38, 76%), alcohol (30, 60%), and the protective effects of cigarette smoking (38, 76%). Most also incorrectly identified the following sexual health factors as risks for EC: early coitarche (30, 60%), or having an abortion (27, 54%), a sexually transmitted infection (35, 70%) or human immunodeficiency virus (34, 68%). Although EC patients recognize that obesity is linked to comorbidities, less than half are aware that it contributes to their cancer risk. Furthermore, responses to lifestyle/sexual health behaviors suggest women may lack understanding of global differences between endometrial and cervical cancer risk factors. Keywords: Endometrial cancer, Obesity, Knowledge, Education